Investor Reaction to the Prospect of Mandatory Audit Firm Rotation - Reid, Lauren C.; Carcello, Joseph V. (The Accounting Review, 2017)
ABSTRACT The PCAOB recently considered implementing mandatory audit firm rotation in hopes of better aligning auditors' interests with investors' interests, suggesting that the PCAOB views long auditor tenure as problematic. However, the accounting profession argues that long tenure actually improves audit quality. This study provides insight into investors' views by evaluating the market's reaction to events related to the potential adoption of rotation that occurred between 2011 and 2013. The results provide some evidence that the market reacts negatively (positively) to events that increased (decreased) the likelihood of rotation, although these results are sensitive to the market index used to calculate abnormal returns. More importantly, particularly given the lack of a U.S.-specific control group, cross-sectional tests provide strong evidence that the market reaction is more negative (positive) on dates that increased (decreased) the likelihood of rotation given longer auditor tenure. Moreover, we also find that the market reaction is more negative (positive) on dates that increased (decreased) the likelihood of rotation given a Big 4 auditor. Data Availability: Data are available from public sources identified in the text.